Tantangan dan Strategi Implementasi SPBE dalam Reformasi Birokrasi Pelayanan Publik di Indonesia - Subhan, Subhan; Sartika, Ika (Dinasti Research, 2025)
This research aims to describe in depth the challenges and implementation strategies of Electronic-Based Government Systems (EBS) in the context of public service bureaucratic reform in Indonesia. Using a descriptive-qualitative approach based on a literature study, this research examines various current data sources from books, scientific journals, and official regulations. The results show that the implementation of SPBE still faces multidimensional challenges, especially in the aspects of ICT infrastructure, system integration, public digital literacy, competence of state civil apparatus (ASN), leadership commitment, and organisational culture. The biggest challenge lies in the limited infrastructure and low digital skills, both among ASN and the general public. To overcome this, suggested strategies include strengthening digital infrastructure evenly, continuous digital competency training, improving cross-sector coordination, and reforming organisational culture towards digitalisation. This research confirms the importance of leadership commitment, policies that favour digital transformation, and a transparent and adaptive SPBE performance evaluation system to support more efficient, responsive, and accountable bureaucratic reforms